In vitro evaluation of enrofloxacin-loaded MLV Liposomes - SEZER, ALİ DEMİR (INFORMA HEALTHCARE, 2007)
Fluoroquinolones are broad-spectrum antimicrobial agents that seem to reach their intracellular target site ( DNA gyrase) in Escherichia coli by means of an uptake process through the outer and inner membranes. Delivery of quinolones with liposomes has many advantages than the free form of the drug. Liposomes may represent an excellent device for improving the selective transport of antibiotics in these respects. In this study, enrofloxacin-loaded multilamellar vesicles (MLVs) were prepared and the effects of formulation variables on the liposome characteristics were investigated. Liposomes were prepared by using the dry lipid film method. A number of variables, such as phospholipid (DL-alpha-phosphatidylcholine dipalmitoyl), cholesterol, enrofloxacin (ENF), stearylamine, and dicetyl phosphate molar ratios and alpha-tocopherol amounts, were studied. The liposome size, encapsulation capacity, drug release, stability, and electrophoretic mobility of ENF-loaded liposomes were determined. Using this method, spherical MLVs with high drug content could be produced. Particle size of liposomes changed between 1.63 and 3.31 mu m and liposome size was affected by all formulation variables ( p < 0.05) except molar ratio of ENF. MLVs can be used as a carrier system for the controlled release of ENF. The highest encapsulation of ENF amount can be obtained using positively charged SA in the formulation and changing the formulation parameters can vary drug release patterns.
Keywords: controlled release; drug encapsulation; enrofloxacin; formulation; liposome; MLV; stability; zeta potential; ENCAPSULATED ENROFLOXACIN; FORMULATION; BEHAVIOR; BILAYERS; DRUGS